2017
DOI: 10.1002/anie.201612472
|View full text |Cite
|
Sign up to set email alerts
|

Redox Self‐Adaptation of a Nitrene Transfer Catalyst to the Substrate Needs

Abstract: The development of iron catalysts for carbon-heteroatom bond formation, which has attracted strong interest in the context of green chemistry and nitrene transfer, has emerged as the most promising way to versatile amine synthetic processes. A diiron system was previously developed that proved efficient in catalytic sulfimidations and aziridinations thanks to an Fe Fe active species. To deal with more demanding benzylic and aliphatic substrates, the catalyst was found to activate itself to a Fe Fe L active spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…This observation is consistent with our previous findings using mono-and dinuclear aminophenolate iron complexes. 69,70 Aiming at evidencing the trend linking aziridination yields (Y) and EA of the active species we have plotted them against each other (Figure 5). It is worth noting that all catalytic aziridination experiments were conducted along the same protocol and that EA of all active species were calculated in the same manner (see Table S13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is consistent with our previous findings using mono-and dinuclear aminophenolate iron complexes. 69,70 Aiming at evidencing the trend linking aziridination yields (Y) and EA of the active species we have plotted them against each other (Figure 5). It is worth noting that all catalytic aziridination experiments were conducted along the same protocol and that EA of all active species were calculated in the same manner (see Table S13).…”
Section: Discussionmentioning
confidence: 99%
“…The monotonous character of the observed trend supports that no steric hindrance plays a significant role in the reaction in spite of notable differences in accessibility between the mono iron aminophenolate complexes where the ligands are tetradentate, the pentadentate ligands of this work and the dinuclear complex. 69,70 The absence of steric influence is probably due to the fact that the charge transfer occurring in the rate determining step does not require a close contact of the two reactants. S10 for electron affinities and aziridination yields values.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, iron has emerged as a ubiquitous metal in the field of catalysis, due to its high abundance, low price and non‐toxicity [33–35] . We reported that the diiron(III,II) catalyst (1) (Scheme S1) is capable to mediate the intermolecular nitrene insertion from an imino‐iodinane (PhI=NTs) to a large range of substrate [36–40] . This complex is able to form aziridine from styrene with a very good yield (87 %) using PhI=NTs at room temperature in dichloromethane for four hours [36,40] …”
Section: Methodsmentioning
confidence: 99%
“…[33][34][35] We reported that the diiron(III,II) catalyst (1) (Scheme S1) is capable to mediate the intermolecular nitrene insertion from an iminoiodinane (PhI=NTs) to a large range of substrate. [36][37][38][39][40] This complex is able to form aziridine from styrene with a very good yield (87 %) using PhI=NTs at room temperature in dichloromethane for four hours. [36,40] In this paper, we first illustrate the effectiveness of Al(OTf) 3 and In(OTf) 3 as Lewis acids for the ring opening of aziridine followed by the insertion of an organic isothiocyanate.…”
mentioning
confidence: 99%
“…As expected, it reacts with tosyliminophenyliodinane to mediate the intramolecular insertion of tosylnitrene onto the benzyl ortho position [22] . Moreover, the analog complex {L[(Py) 2 ][(Py)(BnCl 2 )]Fe III (mpdp)Fe II (MeOH)}(ClO 4 ) 2 with the two ortho benzylic positions protected by chlorine atoms revealed high catalytic activities in tosylnitrene transfers to various substrates: thioanisole, [55] styrene, [55,77–79] ethylbenzene and cyclohexane [24,80] . This justified a detailed investigation of the mechanisms of nitrene generation and transfer.…”
Section: Hydrogen Atom Abstraction and Tautomerismmentioning
confidence: 53%